Two Genes Encoding a Bacterial-Type ATP-Binding Cassette Transporter are Implicated in Aluminum Tolerance in Buckwheat. (17th August 2018) - Che, Jing; Yamaji, Naoki; Yokosho, Kengo; Shen, Ren Fang; Ma, Jian Feng
Abstract: Buckwheat ( Fagopyrum esculentum Moench) shows high tolerance to aluminum (Al) toxicity, but the molecular mechanisms underlying its high Al tolerance are poorly understood. Here, we functionally characterized two genes ( FeSTAR1 and FeSTAR2 ), which encode a nucleotide-binding domain and a membrane domain, respectively, of a bacterial-type ATP-binding cassette (ABC) transporter. The expression of FeSTAR1 and FeSTAR2 was induced by Al in both roots and leaves with higher expression in the roots. Spatial and tissue-specific expression analysis showed that the Al-induced expression of these two genes was found in both the root tips and basal root regions with higher expression in the root outer cell layers. The expression was neither induced by other metals including Cd and La nor by low pH and phosphorus-deficiency. FeSTAR1 and FeSTAR2 were present in a single copy in the genome, but the Al-induced transcript copy number of FeSTAR1 and FeSTAR2 was much higher than their homologous genes in rice and Arabidopsis. FeSTAR1 and FeSTAR2 form a complex when co-expressed in onion epidermal cells. Introduction of FeSTAR1 and FeSTAR2 into Arabidopsis mutants atstar1 and als3 / atstar2, respectively, rescued the sensitivity of the mutants to Al. Taken together, our results indicate that FeSTAR1 and FeSTAR2 are involved in Al tolerance and that their high expression level may contribute to high Al tolerance in buckwheat.